Influence of detection of pretreatment cytogenetic abnormalities on first complete remission and survival in adult acute lymphoblastic leukemia - Milena Georgieva Velizarova; Evgueniy A. Hadjiev; Kamelia V. Alexandrova; Ivanka I. Dimova; Draga I. Toncheva; Nadya E. Dimitrova (Turkish Journal of Hematology, 2011)
OBJECTIVE: Treatment of acute lymphoblastic leukemia (ALL) in adults focuses on the initial assessment of the prognostic relevant cytogenetic features as well as a response-guided therapy based on molecular data. We examined the importance of molecular-cytogenetic abnormalities for complete remission (CR) rates and the overall survival (OS) in adult ALLs. METHODS: Conventional cytogenetics and fluorescence in situ hybridization were performed on bone marrow cells from 33 newly-diagnosed ALL adults. Two karyotype categories [standard- risk group- normal karyotype, hyperdiplody and other structural aberrations, and high-risk group-t(11q23)/MLL, t(9;22)/bcr-abl, t(1;19), t(8;14), C-MYC and complex karyotype] and the biologically and clinically relevant ALL ploidy subgroups were prospectively defined. RESULTS: Chromosomal abnormalities were found in 52% of the cases with a high rate of poor-risk translocations - t(9;22), t(8q24), t(11q23), t(1;19). The total CR rate was 67% and the median time for achievement 2.33 months. Male sex, an age below 35 years and the absence of high risk translocations might have contributed to the high CR rates. Female patients, hyperdiplody, low white blood cells (WBC), and random cytogenetic aberrations had the longest OS. OS, 3- and 5-years survival periods were significantly shorter for poor-risk than standard risk group (p=.015, p=.001 and p=.005, respectively). CONCLUSION: This study emphasizes the lack of influence of cytogenetic aberrations on the CR and the time to achieve CR. However, our observations show that these aberrations are an independent prognostic factor in adult ALL - they allow predicting therapy resistance and the OS time after intense treatment.